Localized topical drug delivery systems for skin cancer: Current approaches and future prospects - Gupta, Nimish; Gupta, G. D.; Singh, Dilpreet (Frontiers in Nanotechnology, 2022)
Topical drug delivery presents a novel substitute to the conventional drug-distribution routes of oral delivery and injection. Apart from the simplicity and non-invasiveness, the skin also serves as a “reservoir” that sustains administration over a period of days. Nanocarriers provide new potential for the treatment of skin disease. The skin’s barrier function offers a considerable obstacle for the potential nanocarriers to infiltrate into the tissue. However, the barrier is partially weakened in case of damage or inflammation, as in the case of skin cancer. Nanoparticles may promote the penetration of the skin. Extensive research has been done into producing nanoparticles for topical distribution; nevertheless, relatively little progress has been achieved in transferring them to the clinic for treating skin malignancies. The prior art features the critical concepts of skin malignancies and techniques in current clinical care. The present review gives a complete viewpoint of the numerous nanoparticle technologies studied for the topical treatment of skin malignancies and outlines the hurdles that hamper its advancement from the bench to the bedside. The review also intends to give knowledge of the routes that control nanoparticle penetration into the skin and their interactions inside the tissue.